A study of sugar cane transportation to the mills in Kanchanaburi, Suphan Buri, Nakhon Pathom and Ratchaburi provinces - Thanu Srichoo (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 1980